Development of an Inquiry-Based Learning Module on the Material of Analyzing the Structure of Negotiation Texts for Class X Vocational School Negeri 2 Mandrehe - Sani Vesti Wita Gulo; Riana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research endeavors to create a learning module aimed at analyzing negotiation text structures, specifically tailored for class X at SMK Negeri 2 Mandrehe. The objective is to ensure the module's feasibility, practicality, and effectiveness. Employing a Research and Development approach, the study adopts a 4D model consisting of Define, Design, Develop, and Disseminate stages. Validation was conducted by three experts—material, language, and design—alongside small and large group testing within the class. Notable progress was achieved through revisions, with the material expert validation reaching 94% in revision II and design expert validation attaining 95.7%. During small group tests, practicality assessments yielded a score of 96.5%, while field trials demonstrated a practicality rate of 93.3%. The module's effectiveness was confirmed with a 100% success rate in small group tests and an 88% success rate in field trials. In summary, this research highlights the development of a comprehensive learning module tailored for class X, focusing on the analysis of negotiation text structures.